A prospective 52 week mucosal healing assessment of small bowel Crohn's disease as detected by capsule endoscopy. (1st December 2014) - Hall, Barry; Holleran, Grainne; Chin, Jun-Liong; Smith, Sinead; Ryan, Barbara; Mahmud, Nasir; McNamara, Deirdre
Abstract: Background: Mucosal healing is increasingly recognised as an important treatment goal in Crohn's disease (CD). Data from colonic disease shows improved long-term outcomes in patients achieving complete mucosal healing. Little is currently known of this with regard to ileitis which is increasingly diagnosed using capsule endoscopy (SBCE). This is the first study to prospectively assess mucosal healing and deep remission rates following 52 weeks of therapy in a cohort of symptomatic small bowel CD patients commencing immunomodulator or biologic therapy. Methods: Baseline demographics, quality of life questionnaires and Harvey Bradshaw Index were collected along with C-reactive protein & calprotectin. Capsule endoscopy Crohn's disease activity (CECDAI) index was used to assess ileitis severity. All parameters were reassessed at week 52. Results at baseline & week 52 were compared using univariate analysis, p < 0.05 considered significant. Results: In total, 108 capsule procedures were performed on 43 patients. Based on the CECDAI, 39 (90%) demonstrated active small bowel CD at baseline with 28 (65%) undergoing 52 week assessment. In total, 12 (42%) participants achieved complete mucosal healing and deep remission by 52 week assessment (p < 0.0001 95% CI − 0.62 to − 0.22). Despite overall impressive mucosal healing rates, patients with strictures were less likely to demonstrate a decrease in CECDAI and were more likely to have symptoms. Conclusion: In patients with active small bowel CD symptomatic and biochemical response to treatment appears to be mirrored by endoscopic remission in 42% of individuals. Strictures identified prior to therapy appear to be a poor indicator for success of treatment.